Can botulinum toxin injection alleviate the pain of bruxism? A Bayesian network analysis and a single-arm analysis - Ao-bo Zhang; Jian-yun Zhang; Xia Zhou; Li-sha Sun; Tie-jun Li (Elsevier, 2024)
Background/purpose: There is inconsistent evidence regarding whether the botulinum toxin A (BTA) injection can relieve pain caused by bruxism. This study aimed to estimate the efficiency of BTA injection in relieving pain caused by bruxism at different follow-up periods. Materials and methods: Five electronic databases were searched from 2005 to 2022 using search terms related to botulinum toxin and bruxism. Only controlled clinical trials were included. Two investigators reviewed each article and discussed any disagreements until a consensus was reached. Pain outcomes as evaluated by the visual analogue scale (VAS) were subjected to single-arm and Bayesian network meta-analyses. Pooling data were measured by a random-effects model. Results: Eleven studies with a total of 365 bruxism patients were included. According to the single-arm analyses of the pooled data, the reduction in bruxism-related pain after BTA injection measured 4.06 points (95% CI = 3.37 to 4.75) on the VAS, and the pain relief was significant in the first 6 months after treatment (P < 0.01). According to the Bayesian analysis, BTA also resulted in significantly greater pain relief than oral splinting (mean difference (MD), −1.5; 95% credible interval (CrI) = −2.7 to −0.19) or saline injection (MD, −3.3; 95% CrI = −6.2 to −0.32). Conclusion: BTA significantly relieves the pain of bruxism for 6 months after injection, and its therapeutic efficacy was higher than that of oral splinting. Nevertheless, further long-term follow-up randomized controlled trials comparing BTA with other management or drugs are warranted.